Iracema e Arnaldo: uma imagem heroica do povo cearense nos romances Iracema e O Sertanejo de José de Alencar - Uchôa, Maria Glacyone Soares (2024)
This study intends to examine the heroic image of the people of Ceará based on the construction of the heroes Iracema (from the novel of the same name) and Arnaldo (from O sertanejo), by José de Alencar. Inspired by longing and loving his homeland and, following the precepts of Romanticism aesthetics, Alencar mythologized the image of the indigenous and country people to affirm the idea of the strength of these people to compose his project of local/national identity defined through homeland symbols: indigenous, countryman, and nature. To achieve his intention, the writer narrates in the pages of Iracema the tragic fate of the Indian warrior, which makes her responsible for the origin of the Brazilian race; and, in O sertanejo, the heroic deeds of the cowboy Arnaldo in the semi-arid region of Ceará, which makes him an example of a fearless man from the backlands. In the two novels, there is no shortage of adventure, courage, honor, and loyalty, in addition to the loving feeling, so evident in the romantic works, which will serve to guide the narrative and reveal the qualities of both heroes. To understand the construction of both heroes from Ceará, we initially did a brief study on the importance of myth in societies; followed by a presentation of the figure of the hero from Homer’s narratives, until we reached the tragic heroine Iracema, and the hero of the Ceará backlands, Arnaldo. Thus, through a detailed study of the Alencarian hero, we will show how the author made use of aspects traditionally found in Greek tragedy and chivalric novels to compose his heroes from Ceará.